2014
DOI: 10.1680/wama.12.00008
|View full text |Cite
|
Sign up to set email alerts
|

A coastal groundwater management model with Indian case study

Abstract: Maity, P. (2014). A coastal groundwater management model with Indian case study. Proceedings of the Institution of Civil Engineers: Water Management, 167 (3), 126-140. A coastal groundwater management model with Indian case study AbstractThe complexity of the hydrogeological setup in coastal areas calls for the adoption of scientific groundwater management techniques. Excessive withdrawal of groundwater in coastal zones will lead to depression of the water table, with associated hazards such as putting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…After Darcy's law of permeability [20], the following correlation holds good: (1) where, i is the hydraulic gradient (=h/L) and k is the hydraulic conductivity. The average flow velocity (v = Q/A) is given by the following correlation:…”
Section: Mathematical Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After Darcy's law of permeability [20], the following correlation holds good: (1) where, i is the hydraulic gradient (=h/L) and k is the hydraulic conductivity. The average flow velocity (v = Q/A) is given by the following correlation:…”
Section: Mathematical Correlationsmentioning
confidence: 99%
“…For growth and sustainability of a country, the optimum usage of water resources is of utmost importance, from the viewpoint of its domestic, agricultural and industrial usages. The fresh groundwater forms the major part of sustainable water resources [1]. Hence, ground water recharge, inter basin water transfer, re-use of water, etc., are the various aspects for adequate water resource planning and management [2].…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies conducted on the influence of rainwater harvesting techniques on runoff and infiltration pattern suggested that itis a widely used groundwater recharge method by storing rainwater in the countries suffered with drought characteristics [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Limitation of water supply, salinity, poor groundwater quality, drought, and groundwater depletion are major difficulties for people to get safe water source. Areas near coastlines with large populations can experience saltwater intrusion due to over groundwater exploitation [1]. Also, tidal waves can flood wells, ponds, and pollute natural sources of freshwater [2].…”
Section: Introductionmentioning
confidence: 99%